2018
DOI: 10.12659/msm.908712
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented QRS (fQRS) Complex Predicts Adverse Cardiac Events of ST-Segment Elevation Myocardial Infarction Patients Undergoing Percutaneous Coronary Intervention and Thrombolysis

Abstract: BackgroundST-segment elevation myocardial infarction (STEMI) is an acute and life-threatening disease. Adverse cardiac events (ACEs) are defined as cardiovascular death or worsening congestive heart failure in STEMI patients. The present study investigated the predictive role of fragmented QRS complex (fQRS) in risks of ACEs in STEMI.Material/MethodsThis study was a retrospective analysis involving patients who underwent percutaneous coronary intervention (PCI) or thrombolysis. STEMI patients were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Then 241 studies were excluded based on title or abstract reading using the predefined eligibility criteria. From the remaining 12 studies that were reviewed in full text, three studies were not included because their endpoints were commingled with atrioventricular heart‐block or polymorphic ventricular extrasystoles, while another 2 were excluded because VTAs were not their observation endpoints. Unlike other studies investigating VTAs during AMI, the study by Lorgis et al investigated VTAs during long‐term follow‐up (846 ± 297 days) and was excluded for protecting our results against bias.…”
Section: Resultsmentioning
confidence: 99%
“…Then 241 studies were excluded based on title or abstract reading using the predefined eligibility criteria. From the remaining 12 studies that were reviewed in full text, three studies were not included because their endpoints were commingled with atrioventricular heart‐block or polymorphic ventricular extrasystoles, while another 2 were excluded because VTAs were not their observation endpoints. Unlike other studies investigating VTAs during AMI, the study by Lorgis et al investigated VTAs during long‐term follow‐up (846 ± 297 days) and was excluded for protecting our results against bias.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of fQRS might indicate severe myocardial insult in AMI patients [3]. Previous studies demonstrated that fQRS was related to higher major adverse cardiovascular events (MACE) in patients with AMI [4][5][6][7][8]. Cardiac autonomic nerve function could be non-invasively assessed by heart rate variability (HRV) [9].…”
Section: Introductionmentioning
confidence: 99%